2018
DOI: 10.1186/s13287-018-0832-2
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell-derived mitochondria transplantation: a novel strategy and the challenges for the treatment of tissue injury

Abstract: Damage of mitochondria in the initial period of tissue injury aggravates the severity of injury. Restoration of mitochondria dysfunction and mitochondrial-based therapeutics represent a potentially effective therapeutic strategy. Recently, mitochondrial transfer from stem cells has been demonstrated to play a significant role in rescuing injured tissues. The possible mechanisms of mitochondria released from stem cells, the pathways of mitochondria transfer between the donor stem cells and recipient cells, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 88 publications
1
61
0
2
Order By: Relevance
“…40 Clinical transplantation of mitochondria between cells is an active area of research but the specific mechanisms and critical factors involved in natural mitochondria transfer between the donor cells and recipient cells remain to be fully characterized. 41 We speculate that mitochondrial clearance and degradation occurs principally by phagocytosis. This study is the first showing free structurally intact mitochondria in plasma, but it is not yet known how they are degraded there, in contrast to intracellular mitophagy, which is well described.…”
Section: Discussionmentioning
confidence: 93%
“…40 Clinical transplantation of mitochondria between cells is an active area of research but the specific mechanisms and critical factors involved in natural mitochondria transfer between the donor cells and recipient cells remain to be fully characterized. 41 We speculate that mitochondrial clearance and degradation occurs principally by phagocytosis. This study is the first showing free structurally intact mitochondria in plasma, but it is not yet known how they are degraded there, in contrast to intracellular mitophagy, which is well described.…”
Section: Discussionmentioning
confidence: 93%
“…To assess the cause-effect relationship for mitochondrial dysfunction in SCZ, Robicek et al [ 84 ] most recently investigated mitochondria transfer to SCZ-iPSC derived neurons [ 78 ]. Several studies have shown that mitochondria can transfer between cells via various contact modes, comprising cell fusion, junction, and tunneling nanotube formation [ 103 ]. In support of these findings, Robicek et al observed that in vitro isolated active normal mitochondria (IAN-MIT) can enter various cell types without any manipulation and stay active.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria-targeting treatment, considered to be an appealing strategy for the control and management of mitochondrial injury [41], has become the focus of many important research studies [42]. Previously-published data have suggested that the injection of isolated viable respiration-competent myocardial mitochondria into ischemic regions prior to reperfusion may reverse post-ischemic functional deterioration and apoptosis, thereby limiting the infarct area [43].…”
Section: Discussionmentioning
confidence: 99%